Strip Cropping Suits for Small Farm Mechanization - Reddy, Y. Pavan Kumar; Reddy, B. Sahadeva; Jyothi, V. Siva; Chandrika, V. (Chronicle of Bioresource Management, 2023)
Farmer’s livelihood is linked with the monsoon in the rainfed province. The monotony of the cropping pattern with giant investment coupled with dry spells impedes the farmer’s economic and mental stability. To overcome crop failure and losses, it’s high time to adopt crop diversification rather than monocropping. Though the crop diversification with the traditional way may not be advantageous to the farmer,however strip cropping is an alternative old age practice that can be modified for its suitability to modern farm mechanization. Thus, it has an edge over other intercropping systems under Indian conditions. Strip cropping can address various issues by utilizing all-natural resources through spatial, temporal, and genetic diversity in one platform to reap a big harvest compared to the sole and inter-cropping systems.